Diversity, pathogenicity, and current occurrence of bacterial wilt Bacterium Ralstonia solanacearum in Peru - Gutarra, L.; Herrera, J.; Fernández, E.; Kreuze, Jan F.; Lindqvist-Kreuze, H. (Frontiers Media, 2017)
The current bacterial wilt infestation level in the potato fields in the Peruvian Andes was investigated by collecting stem samples from wilted plants and detecting Ralstonia solanacearum. In total 39 farmers’ fields located in the central and northern Peru between the altitudes 2111 and 3742 m above sea level were sampled. R. solanacearum was detected in 19 fields, and in 153 out of the 358 samples analyzed. Phylogenetic analysis using the partial sequence of the endoglucanase gene on strains collected in Peru between 1966 and 2016 from potato, pepper, tomato, plantain or soil, divided the strains in phylotypes I, IIA, and IIB. The Phylotype IIB isolates formed seven sequevar groups including the previously identified sequevars 1, 2, 3, 4, and 25. In addition to this, three new sequevars of phylotype IIB were identified. Phylotype IIA isolates from Peru clustered together with reference strains previously assigned to sequevars 5, 39, 41, and 50, and additionally one new sequevar was identified. The Phylotype I strain was similar to the sequevar 18. Most of the Peruvian R. solanacearum isolates were IIB-1 strains. In the old collection sampled between 1966 and 2013, 72% were IIB-1 and in the new collection at 2016 no other strains were found. The pathogenicity of 25 isolates representing the IIA and IIB sequevar groups was tested on potato, tomato, eggplant and tobacco. All were highly aggressive on potato, but differed in pathogenicity on the other hosts, especially on tobacco. All IIA strains caused latent infection on tobacco and some strains also caused wilting, while IIB strains caused only few latent infections on this species. In conclusion, high molecular diversity was found among the R. solanacearum strains in Peru. Most of the variability was found in areas that are no longer used for potato cultivation and thus these strains do not pose a real threat for potato production in the country. Compared to the previous data from the 1990s, the incidence of bacterial wilt has decreased in Peru. The epidemics are likely caused by infected seed tubers carrying the clonal brown rot strain IIB-1.